Is Facebook A Ride-Sharing Platform? Exploration Through Affordance Theory - Santa, Mijalche; Ciunova shuleska, Anita (My University, 2019)
Peer-to-peer ride-sharing is one of the most complex archetype of the sharing economy. As a result, dedicated digital platforms, designed specifically to handle this complexity, have emerged. However, there are practices where Facebook is used to organise the ride-sharing, although it lack features that can handle the complexity of ride-sharing. In this research-in-progress paper we demonstrate the importance for researching these practices. We justify the appropriateness for using the Affordance - actualisation lens for analysing the practices. We present the preliminary results from the first case study research.
Keywords: Facebook, Sharing economy, Ride-sharing, Affordance theory